Effects of Defrost-Initiation Criteria and Orientations of an Outdoor Heat Exchanger on the Performance of an Automotive Reversible CO2 Heat Pump - Wenying Zhang; Wenzhe Li; Pega Hrnjak (Energies)
Heat pump (HP) technology has been widely adopted in electric vehicles (EVs) for cabin and battery heating in cold weather due to its high efficiency. However, when an HP works under low ambient temperatures and high humidity, frost grows on the surface of the outdoor evaporator, deteriorating system efficiency. This study experimentally investigated the performance of an automotive reversible CO2 HP system under cyclic frosting–defrosting conditions, with different defrost-initiation criteria and orientations of the outdoor heat exchanger. The relationship between the performance degradation of the heat pump system and the feature of frost accumulation on the outdoor heat exchanger is analyzed. The experimental data revealed that the heating capacity of the HP system only mildly degrades (~30%), even with an air-side pressure drop of the outdoor heat exchanger growing 10 times, which enables the system to work in HP mode for a longer time before the defrosting without significantly impacting passengers’ comfort. The horizontally installed outdoor heat exchanger is proven to have better refrigerant distribution, but with approximately a 0.16 bar (11.9%) higher pressure drop, reducing the evaporating temperature by about 0.4 K. Consequently, frost accumulates faster, and the working time in HP mode is shortened by 12 min (18.2%). Moreover, the vertical outdoor heat exchanger drains much more water during the defrosting. As a result, the defrosting time for the vertical outdoor heat exchanger is reduced by 17%.